Способ экстракционной переработки высокоактивных отходов с фракционированием радионуклидов - Гаврилов П. М. Петр Михайлович; Ревенко Ю. А. Юрий Александрович; Алексеенко С. Н. Сергей Николаевич; Алексеенко В. Н. Владимир Николаевич; Бондин В. В. Владимир Викторович; Бычков С. И. Сергей Иванович; Кривицкий Ю. Г. Юрий Григорьевич; Дьяченко А. C. Антон Сергеевич
опубл. 10.02.13